Pengenalan Cyber Security Sebagai Fundamental Keamanan Data Pada Era Digital - Amin Hidayat; Meidy Fajar Wahyu; Yuda Samudra (CV. Multi Kreasi Media, 2023)
Cyber ​​crime is a relatively new crime, which is carried out by people who are experts or who have expertise in the field of computers and information technology. When viewed from the perspective of crime, crime through cyberspace (internet) can have an impact inside and outside the virtual world. The limited space and time in carrying out activities using the internet as a medium makes it difficult for an activity in cyberspace to be detected conventionally. In the case of cyber threats, based on data analysis of the ID-SIRTII (Indonesian Security Incident Response Team On Internet Infrastructure) traffic monitoring system, it was noted that the incidence of cyber attacks in Indonesia has reached one million incidents and will increase every day due to system and application weaknesses that do not exist. is known. Protecting digital assets is an important concern, as cyber attacks affect a company's performance and reputation. Many methods and techniques can be used to support the process of directing students to take advantage of great opportunities with the impact of the development of internet technology. One of the introductions to Cyber ​​Security and how to enter personal data on gadget devices that currently students are good at using these devices, but still lacks knowledge about data security. With the introduction of cyber security as fundamental data security in the digital era, it is hoped that students will have an awareness of the importance of personal data so that data does not occur by irresponsible people so as to harm various parties whose data is misused. So, this Community Service Activity aims to provide direction to students by conducting face-to-face counseling with students to introduce the importance of data security in the digital era and support understanding of cyber security and cyber crimes that occur in the current era. This activity is in the form of training materials and practices during the training. The material contains a basic introduction to the impact of training on the advancement of internet technology, how to implement data security, and the application of safe e-commerce usage for personal data security. In preparation for the training, the service team tested the application of data in the use of e-commerce as material which was then discussed during the training. The training was given in the form of a lecture followed by a question and answer session. Starting from the introduction of the impact of post-advancement internet technology, then they will be taught how to apply security data to digital products when transacting online, so that the way the data is known by many people, then students will also be provided with practices on how to use security systems on gadgets and understand how to flow. secure transactions on websites, e-commerce and games. The training was held in the Computer Lab of Madrasah Aliyah Negeri 1, South Tangerang City, so that students could immediately practice what they were learning in this training. Keywords: Cyber Security, Keamanan Data, Era Digital, Data, Cyber Crime